Angiomatoid fibrous histiocytoma in an elderly male: An unusual presentation with review of literature (Indian Journal of Case Reports, 2018)
Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor occurring mostly in children, adolescents, and young adults. Clinically and radiographically, it is difficult to differentiate AFH from hematoma, soft tissue hemangioma, and malignant fibrous histiocytoma. Here, we present the clinical, radiologic, and pathologic findings of a case of AFH due to its rarity in a 67-year-old man. The patient underwent wide surgical excision with a provisional diagnosis of sarcoma. On pathological examination, the lesion demonstrated solid-cystic nodules of histiocytes with blood-filled cysts, a dense hyaline fibrous pseudo capsule, and a very focal peripheral lymphoplasmacytic infiltrates. The tumor cells showed strong positivity for CD68, variable positivity for CD34, Desmin, EMA, negativity for CK and a low Ki67 index.